Properties of Two Enzymes Involved in the Phosphoinositide Cycle – Diacylglycerol Kinase and Phosphatidylinositol 4-Phosphate 5-Kinase - Shulga, Yulia V. (My University, 2012)
The two lipid kinases, diacylglycerol kinase (DGK) and phosphatidylinositol 4-phosphate 5-kinase (PIP5K), are vital players of the phosphatidylinositol cycle. DGK regulates the intracellular balance between two important lipid signaling molecules, diacylglycerol and phosphatidic acid. PIP5K produces another key signal messenger, phosphatidylinositol 4,5-bisphosphate. We studied several fundamental aspects of DGK and PIP5K properties. We investigated the topology of the hydrophobic segment of FLAG-tagged DGK epsilon, and showed that a single amino acid mutation P32A caused the hydrophobic segment to favor a transmembrane orientation. We demonstrated that DGKε is localized in both the plasma membrane and endoplasmic reticulum. Our work helped to better elucidate the substrate specificity of DGKε and PIP5K isoforms, and it lead us to discover the motif that is common for several enzymes that exhibit specificity for substrates containing polyunsaturated fatty acids. We studied the organ distribution of murine DGK isoforms, and also expanded our knowledge of DGK expression in diabetic animals, showing that the expression profiles of several DGK isoforms are altered in adipocytes isolated from diabetic mice. Moreover, DGK expression profiles change dramatically during adipocyte differentiation. Taken together, our findings contribute to the growing knowledge about two enzymes, DGK and PIP5K, by providing the fundamental information about the structural and functional properties of these lipid kinases. Both PIP5K and DGK enzymes have a strong potential for use as drug targets. Although at present their clinical importance has not been completely assessed, we believe that their significance as drug targets will be recognized in the nearest future.
Keywords: phosphoinositide cycle; diacylglycerol kinase; acyl chain specificity; Biochemistry; Biochemistry